Blockchain Technology: Ensuring Data Integrity and Security in Modern Enterprise Systems - Sharath Chandra Adupa (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores blockchain technology’s transformative role in ensuring data integrity and security across modern enterprise systems. The article examines the fundamental architecture of blockchain security, emphasizing distributed ledger technology, consensus mechanisms, and cryptographic foundations that collectively create an immutable and transparent system. The article investigation delves into core security features, including the implementation of advanced cryptographic techniques, decentralization strategies, and innovative security protocols that protect against various cyber threats. Through detailed analysis of industry applications, the article demonstrates blockchain’s impact across financial services, supply chain management, healthcare, and IoT sectors, highlighting significant improvements in operational efficiency, security, and cost reduction. The article further evaluates implementation benefits, encompassing operational advantages, economic impacts, and technical improvements that organizations experience through blockchain adoption. Finally, the article addresses future implications and challenges, including technology integration hurdles, regulatory considerations, and scalability solutions, providing insights into the evolving landscape of enterprise blockchain implementation.